Case of Cardiac Arrest Treated with Extra-Corporeal Life Support after MDMA Intoxication - Pierre Voizeux; Romain Lewandowski; Theresa Daily; Omar Ellouze; Olivier Bouchot; Belaïd Bouhemad; Pierre-Grégoire Guinot (Case Reports in Critical Care)
Objective. To describe the case of a patient who developed a serotonin syndrome due to a 3,4-methylenedioxymethamphetamine ingestion with electrical storm and refractory cardiac arrest. Design. Case report. Study Selection. ICU of a university hospital. Patient. A 22-year-old man transferred to the emergency room with hyperthermia, tremors, and mydriasis presented a cardiac arrest due to ventricular fibrillation. Interventions. We implemented extra-corporeal life support combined with vasoactive drugs. Later, he also benefited from renal replacement therapy and mechanical ventilation. Measurements and Main Results. We were able to rapidly regulate our patient’s temperature and we weaned all hemodynamic support in the first week of hospitalisation. Conclusion. Extracorporeal life support has several advantages as part of the management of hemodynamic instability induced by serotonin syndrome.